Natureza e sensibilidade, em Feuerbach: delineamentos de uma antropologia integral - Rodrigues, Rodrigo da Silva (2019)
The dissertation aims to clarify Feuerbach’s conception of nature and sensibility, as fundamental elements for an anthropological philosophy, considering man in its entirety constituted of head and heart, highlighting his capacity of thinking, wishing and feeling. His major criticisms refer to Hegel’s religion and idealistic system, as a counterpoint, the German author praises the nature and the sensibility as relevant aspects to think about a new man and a new philosophy. Criticizing religion as a representation of human essence, Feuerbach does not want to deny God, but to state man in his completeness. But to do so, nature and sensibility become foundational elements not only of a new philosophy, but of a new way to see the world and himself, promoting a rescue of his own body and of the human essence. The philosopher also highlights a new concept of individuality that does not carry out itself, but in the coexistence with the other and the world, starting to humanize relationships and think about reconciliation of life. By showing the sensibility, the body and the nature. Feuerbach ends up establishing an anthropological materialism. Therefore, the author presents it in an inaugural way, a critical philosophy as far as he seeks to problematize and criticize German idealism that conceived a displaced existence thought that he thinks about himself. His religious deconstruction and his abstract critical way of thinking have become affirmations of life, humanizing the actions that nowadays are aimed and centered in the existence